Education on Slow Deep Breathing Therapy for Hypertensive Elderly Anxiety Management in Baitussalam - Cut Fitri Rahmayati; Lili Kasmini; Eridha Putra (International Journal of Multidisciplinary Sciences and Arts, 2026)
Hypertension is one of the most prevalent chronic diseases among older adults and is frequently associated with anxiety, which may negatively affect blood pressure control, treatment adherence, and overall quality of life. Anxiety that is not properly managed can also increase the risk of cardiovascular complications and reduce the effectiveness of hypertension management. Therefore, providing education on non-pharmacological interventions is essential to enhance older adults' knowledge and self-management capabilities. This study aimed to analyze the effect of slow deep breathing education on improving knowledge regarding anxiety management among older adults with hypertension. A quantitative study employing a quasi-experimental one-group pretest-posttest design was conducted involving 70 older adults with hypertension selected through total sampling from the working area of the Baitussalam Community Health Center, Aceh Besar. Participants received structured educational sessions on slow deep breathing techniques as a complementary strategy for anxiety management. Knowledge was assessed using a validated structured questionnaire administered before and after the intervention. The collected data were analyzed using the Wilcoxon Signed-Rank Test to determine differences in knowledge scores between the pretest and posttest. The results demonstrated a statistically significant improvement in participants' knowledge following the educational intervention (p < 0.001), indicating that the program effectively increased their understanding of anxiety management through slow deep breathing. These findings suggest that slow deep breathing education represents an effective, practical, and community-based health education strategy for enhancing knowledge and promoting anxiety self-management among older adults with hypertension, thereby supporting comprehensive and holistic hypertension care.